A production method for improving the fluidity of inorganic mineral powder

By controlling the particle size and grading the inorganic mineral powder, the problem of poor fluidity of inorganic mineral powder is solved, and the effect of reducing energy consumption and production costs is achieved.

CN118768062BActive Publication Date: 2025-04-25JIANGSU HENGFENG NENGHUAN TECH CORP LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411038040.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-04-25
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The existing inorganic mineral powder production methods lead to poor powder flowability, resulting in increased equipment energy and electricity consumption, large amount of additives during the production process, and low product quality and stability.

Method used

By controlling the particle size of the inorganic mineral powder, the powder A, powder B and powder C of different particles are collected in a graded manner, and the mass ratio between powder B and powder C is controlled to improve the fluidity of the powder.

Benefits of technology

It improves the fluidity of inorganic mineral powder, reduces the energy and power consumption of equipment, reduces the amount of additives in the production process, and achieves the effect of reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118768062B_ABST
    Figure CN118768062B_ABST
Patent Text Reader

Abstract

The present invention provides a production method for improving the fluidity of inorganic mineral powder, comprising the following steps: crushing the inorganic mineral raw material so that the crushing rate reaches more than 90%, then using gravity and buoyancy to grade and collect inorganic mineral powders of different particles, the collected powder A 100wt% particle size is less than 20 mesh, and it is returned to be combined with the inorganic mineral raw material for crushing, the collected powder B particle size is 20-120 mesh accounting for ≥80wt%, the powder C particle size is greater than 100 mesh accounting for ≥80wt%, and the mass ratio between powder B and powder C is controlled between (8:2) and (6:4); the powder C is further ground to a particle size greater than 300 mesh accounting for more than 80wt%, and mixed with the powder B. The present invention can improve the fluidity of inorganic mineral powder, and the production method is applicable to all inorganic mineral powders, such as the production of non-metallic mineral powders such as barium carbonate and barium titanate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic mineral powder production, in particular to a production method for improving the fluidity of inorganic mineral powder. Background Art

[0002] Inorganic mineral powders are mainly made of inorganic mineral raw materials in nature. According to their composition and properties, they can be divided into many types, such as quartz powder, talcum powder, calcium carbonate powder, wollastonite powder, mica powder, etc. For example, common barium carbonate, barium titanate and other non-metallic mineral materials are all common inorganic minerals.

[0003] With the continuous advancement of science and technology and the improvement of environmental awareness, the market demand for inorganic mineral powders continues to grow. Especially in the development of high-performance, environmentally friendly products, the application prospects of inorganic mineral powders are even broader. In the future, with the continuous improvement of preparation technology and the continuous discovery of new inorganic mineral resources, the types and properties of inorganic mineral powders will be more diversified, and the application fields will be further expanded.

[0004] The production method of inorganic mineral powder in the prior art mainly adopts the method of crushing and grinding. However, the inorganic mineral powder produced by this traditional production method has poor fluidity during pipeline transportation, which will lead to increased energy consumption and electricity consumption of the equipment. Due to the fluidity, the amount of medicine used in the production process will also be relatively large, and the quality of the product cannot be maintained at a relatively high level, and the stability is also poor.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a production method for improving the fluidity of inorganic mineral powders. The method improves the fluidity of the powder by controlling the particle size of the powder in the entire production method. By improving the fluidity of the powder, the energy consumption and power consumption of the equipment are reduced, and the amount of additives used in the production process is also reduced, which can achieve the effect of reducing production costs for production enterprises. The production method is applicable to the production of all inorganic mineral powders, such as barium carbonate, barium titanate and other non-metallic mineral powders.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The invention provides a production method for improving the fluidity of inorganic mineral powder. The inorganic mineral raw material is crushed to achieve a crushing rate of more than 90%, and then inorganic mineral powders of different particles are collected by classification using gravity and buoyancy. 100wt% of the collected powder A has a particle size of less than 20 meshes, and is returned to be combined with the inorganic mineral raw material for crushing. The collected powder B has a particle size of 20-120 meshes, accounting for ≥80wt%, and the powder C has a particle size greater than 100 meshes, accounting for ≥80wt%, and the mass ratio of the powder B to the powder C is controlled between (8:2) and (6:4).

[0009] Here, there are very clear limits on the mesh size of powder B and powder C. The reason is that if the particle size of powder B is too large, it cannot be perfectly filled when mixed with powder C later, and there will be gaps that will affect the fluidity. Similarly, the particle size of powder C cannot be too small, because if the particle size of powder C is too fine, it will cause overfilling. During the flow process, it will all be wrapped around the outside of powder B, reducing the fluidity of powder B. Therefore, when mixing, not only powder B needs to be within the appropriate particle size range, but also powder C needs to be within the appropriate particle size range. The particle size of this preferred range must account for the larger the proportion of the entire powder, the better. Therefore, here it is required that the particle size of powder B is 20-120 mesh and accounts for ≥80wt%, and the particle size of powder C is greater than 100 mesh and accounts for ≥80wt%. Because after the proportion reaches ≥80wt%, after the two powders are mixed, large particles and small particles can form a perfect ratio, and the filling is more sufficient. The above parameters are also the best ranges found after specific practice based on the types of various inorganic mineral powders. Generally, the powder C needs to be further finely ground until the particle size is greater than 300 mesh and accounts for more than 80 wt %, and then mixed with the powder B to achieve the purpose of the present invention.

[0010] The reason why the mass ratio of powder B to powder C needs to be controlled between (8:2) and (6:4) is that at this ratio, powder C can be fully filled into the gaps in powder B, thereby reducing the friction between particles of the same size in the powder. If the proportion of large particles is too high during the flow process, the friction between the same particles will increase. In this way, by combining small particles with a certain mass ratio, they can be filled into the gaps in the large particles, and the interactive friction will be converted into rolling friction. However, the amount of combination needs to be appropriate, because whether it is too many large particles or too many small particles, perfect filling cannot be achieved. Of course, the specific appropriate mass ratio between large particles and small particles requires a lot of creative labor. Only after a lot of practice can the optimal mass ratio range be known.

[0011] In the scheme of the present invention, the powder is graded according to the particle size during the production process of the inorganic mineral powder. Through continuous exploration, it is found that the inorganic mineral powder prepared by the above-mentioned grading method of the present invention has better fluidity, because it is found through experiments that when the powder C is ground to a particle size greater than 300 mesh, especially when the proportion of this particle size reaches more than 80wt%, the particle size difference between the powder C and the powder B is widened. The ultra-low friction and viscosity of the powder C are used to improve the fluidity of the overall inorganic mineral powder.

[0012] Preferably, as a further feasible solution, the powder C is further ground until more than 80wt% is between 350 mesh and 600 mesh. When more than 80wt% of the powder C can be controlled within the range of 350 mesh to 600 mesh, the effect of improving fluidity is the best. Of course, this range means that the particle size range cannot be too large or too small, because if the particle size of the powder C is too large, its friction and viscosity cannot be optimal, and it cannot play the desired effect after mixing with the powder B. When the particle size of the powder C is too small, it means that it is ground too finely, increasing the friction between the particles in the powder. Too many particles of the same particle size will also reduce fluidity.

[0013] Preferably, as a further feasible scheme, in the process of grading by gravity and buoyancy, the falling material is first divided into 5 components by an accelerated jet, and then the powders of different components are further sieved according to the mesh size to obtain powder A, powder B, and powder C, so as to improve the accuracy of the powder particle size distribution in the whole process.

[0014] Because if the method of direct screening is adopted to obtain powder A, powder B, and powder C, the accuracy is not high, and the particle size ratio and the mass ratio between the powders cannot be accurately controlled. Therefore, the present invention adopts the method of first screening out 5 components. These 5 components are accelerated by means of an accelerated jet so that the parameters of the accelerated jet correspond to the particle size of the components to a certain extent, thereby controlling the particle size of each of the 5 components screened out to be within the expected range.

[0015] Preferably, as a further implementable scheme, the injection rate of the accelerating jet is adjusted by fixing the injection air volume and adjusting the injection pressure of 150-300KPa, so that it is divided into 5 components according to the particle size through different injection rates, wherein the particle size of the first component is less than 20 mesh, the particle size of the second component is 20-40 mesh, the particle size of the third component is 40-100 mesh, the particle size of the fourth component is 100-200 mesh, and the particle size of the fifth component is greater than 300 mesh.

[0016] The above scheme is to control the injection pressure within a certain range so that the injection pressure is changed within this range to obtain the particle sizes of the corresponding five components.

[0017] Preferably, as a further feasible solution, the first component and the second component particles smaller than 20 mesh are mixed to obtain powder A, the second component particles larger than 20 mesh, the third component and the fourth component particles smaller than 120 mesh are mixed to obtain powder B, and the remaining fourth component and the fifth component are mixed to obtain powder C. The above 5 components are all accurately distributed to powder A, powder B, and powder C by the material distribution valve.

[0018] By first dividing into 5 components as mentioned above, and then mixing them to form powder A, powder B, and powder C respectively, such a process can ensure that the particle size of powder B is 20-120 mesh, accounting for ≥90wt%, and the particle size of powder C is greater than 100 mesh, accounting for ≥90wt%, and the mass ratio between powder B and powder C is controlled between 7.4:2.6, which is equivalent to further improving the proportion of ideal particle size in powder B and powder C, and can further achieve the purpose of improving inorganic mineral powder. Because according to the above discussion, the larger the proportion of powder in the preferred mesh particle size range is, the more conducive it is to the filling property after subsequent mixing, and the more fully the filling is, the better the fluidity is naturally improved. Therefore, through the method of first screening the 5 components of the present invention, the proportion of the particle size distribution of powder B and powder C can be more accurately controlled.

[0019] Preferably, the fixed injection air volume for each classification is 20000Nm 3 / h, when the first-stage graded injection pressure is controlled at 300-350KPa, the particle size of the first component is less than 20 mesh, and the particle size of the second component is 20-40 mesh;

[0020] When the secondary graded injection pressure is controlled at 200-230 KPa, the particle size of the third component is 40-100 mesh;

[0021] The three-stage graded injection pressure is controlled at 150-180KPa, the particle size of the fourth component is 100-200 mesh, and the particle size of the fifth component is greater than 300 mesh. The optimal injection pressure corresponding to each component has finally reached a quantitative result through a large number of creative practices, so that by controlling a certain injection pressure, the component with the required particle size can be obtained accordingly.

[0022] The present invention also provides a production method and production equipment for improving the fluidity of inorganic mineral powder, comprising: a raw material bin, and a crusher connected to the raw material bin, the crusher is connected to a wind classifier for classifying the crushed powder, and the bottom of the wind classifier is correspondingly provided with a bin A for collecting powder A, a bin B for collecting powder B, and a bin C for collecting powder C;

[0023] The silo C is connected to a first kneading machine and an ultrafine grinder in sequence, the silo B is connected to a second kneading machine, and the ultrafine grinder is connected to the second kneading machine to mix the ground powder C with the powder B.

[0024] The whole production process of the present invention is as follows:

[0025] Powder making process: The raw materials are stored in the raw material warehouse, and then fall into the belt weighing scale by gravity for transportation and weight measurement. The crusher adjusts the speed according to the falling materials, and uses the ultra-high speed of the crusher turntable to accelerate the hammer installed on the turntable to rotate at high speed. The high-speed rotating hammer hits the raw materials falling from top to bottom. The raw materials are broken after being hit by the high-speed rotating hammer and rebound to the impact plate of the crusher inner cylinder for secondary crushing. After that, they fall down with the action of gravity, and are hit again and repeatedly by the second layer of hammers. Finally, they fall down due to the action of gravity and are broken into powder.

[0026] Grading and powder selection process: The powder obtained in the powder making process falls freely into the feeding end of the wind classifier due to gravity. The wind classifier is divided into three levels. A fixed amount of air (nitrogen or carbon dioxide can also be used) is blown into each level to screen the falling powder. The rate of the accelerating jet is controlled by adjusting the accelerating jet pressure. In this way, due to the different particle sizes of the powders, the powders fall in different positions and fall into different silos according to their weights. At this time, the first silo to the fifth silo are set between the wind classifier and the silo A for collecting powder A at the bottom, the silo B for collecting powder B, and the silo C for collecting powder C. In this way, the five silos collect powders of different particle sizes.

[0027] In this way, heavier powders have the shortest jet distance and are most likely to fall on the left silo of the wind classifier. Lighter powders are more likely to fall on the right side of the wind classifier. The lightest powders follow the airflow into the dust collector and fall into the last silo. The wind classifier can adjust the blower pressure to select powder according to the material load from the crusher and its own needs. The above measures can achieve the classification of all powders in order according to particle size.

[0028] After classification from the first silo to the fifth silo, the powder can be discharged through the silo discharge valve and pipeline to the three lower silos, namely silo A, silo B and silo C. Among them, the powder in silo A is unqualified powder and returns to the crusher for secondary crushing. The powder collected by silo B is 20-120 mesh, accounting for ≥80wt%, and the powder collected by silo C is larger than 100 mesh, accounting for ≥80wt%. The overall mass ratio of powder B and powder C is controlled between (8:2) and (6:4).

[0029] Grinding process: The powder C in the silo C is weighed by the discharge valve and the weighing device, and then mixed and stirred uniformly with the measured water in the first kneading machine, and then sent to the ultrafine grinder for ultrafine grinding, so that the particle size is reduced to more than 300 meshes and accounts for more than 80wt%, and mixed with the powder B. The above process improves the fluidity of the inorganic mineral powder. For the production enterprise, the investment and energy consumption of preparing the inorganic mineral powder by adopting the method of the present invention are reduced by more than 30%.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The production method effectively improves the fluidity of inorganic mineral powders. The method of controlling the particle size of the powder in the entire production method improves the fluidity of the powder. By improving the fluidity of the powder, the energy consumption and power consumption of the equipment are reduced, and the amount of additives used in the production process is also reduced. For production enterprises, it can achieve the effect of reducing production costs;

[0032] (2) The production equipment used in the present invention to improve the fluidity of inorganic mineral powder is simple in process and easy to operate. The inorganic mineral powder prepared by this production process has good fluidity, which effectively improves production efficiency and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0034] Picture 1 This is a specific process flow chart of the production method for improving the fluidity of inorganic mineral powders according to Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The embodiments of the present invention will be described in detail below in conjunction with examples. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] Example 1

[0037] like Picture 1 As shown, the spodumene mineral is taken as an example, and the overall process is divided into the crushing stage, the powder selection stage, and the grinding stage;

[0038] Crushing stage: spodumene is stored in the raw material warehouse, and the coal is dropped onto the belt scale with metering function through the raw material discharge valve, and transported to the top of the crusher, and the material is dropped into the crusher inlet by gravity. After the spodumene falls into the crusher, the speed is adjusted to 70-80%, and the linear speed is controlled to 120m / s. The spodumene particles are hit and crushed by the high-speed rotating hammers, and then rebound to the rebound impact plate of the crusher lining for secondary crushing. Then, due to the gravity, it falls downward, enters the second layer of hammers and hits, and rebounds to the impact plate again. The crushing rate reaches more than 90%, and the unqualified material A (particle size greater than 20 mesh) is only 5-8%. The speed is adjusted to 90%, the linear speed is increased to 140m / s, and the unqualified material A (particle size greater than 20 mesh) is only 2-6%. The speed is further increased to 100%, the linear speed is increased to 160m / s, and the unqualified material A (particle size greater than 20 mesh) is only 1-3%. Through the above adjustments, it can be seen that as the speed increases, the total amount of unqualified material A (particle size greater than 20 mesh) decreases, that is, the return ratio will further decrease as the speed increases. Therefore, different materials should choose the appropriate speed. In addition, the higher the speed, the greater the wear, and the life of the hammer will be reduced as the speed increases.

[0039] In addition, as the crusher speed increases by 100%, the feed volume increases to the full load of the equipment. At this time, the return ratio will increase relatively, that is, the number of unqualified materials will increase. After multiple debugging, the speed of 70-80% was finally selected as the most appropriate, and the return ratio was less than 5%.

[0040] Powder selection stage: After crushing, the material enters the wind classifier by gravity for classification and screening. The fixed three-level injection air volume is 20000Nm 3 / h, when the first-level classification jet pressure of the wind classifier is controlled at 300-350KPa, the first component and the second component are obtained. When the second-level classification jet pressure of the wind classifier is controlled at 200-230KPa, the third component is obtained. When the third-level classification jet pressure of the wind classifier is controlled at 150-180KPa, the fourth component and the fifth component are obtained. Components of different particle sizes (weights) fall into silo 1, silo 2, silo 3, silo 4, and silo 5 respectively. The particle size distribution of each silo after analysis is shown in Table 1. The values ​​​​reflected in Table 1 are the screening rates corresponding to the particle sizes. For example, it can be seen from Table 1 that silo 5 can account for 92.04% of particles larger than 300 mesh. The specific particle size distribution of other silos can also be known from the specific screening rate records.

[0041] Table 1 Screening rate of 5 silos

[0042]

[0043]

[0044] The materials in silo 1 and part of silo 2 enter silo A and return to the crusher. Part of silo 2, silo 3 and part of silo 4 enter silo B, and part of silo 4 and silo 5 enter silo C. At this time, the ratio of B:C is exactly 7.4:2.6, and the particle size of powder B is 20-120 mesh, accounting for ≥90wt%, and the particle size of powder C is greater than 100 mesh, accounting for ≥90wt%.

[0045] Grinding stage: According to the above particle size analysis data, it can be seen that the total average particle size of silo C has not yet reached the requirement, and further grinding is required, especially the material in silo C needs to be significantly ground, and finally more than 90wt% of the particles are larger than 300 mesh. After weighing and metering, silo C is stirred and mixed with the mixed liquid in the first kneader, and then sent to the ultrafine grinder for further deep grinding, so that the powder C with a particle size larger than 300 mesh accounting for ≥90wt% is obtained.

[0046] Mixing stage: The ground powder C is sent to the second kneader after being measured, and mixed with the powder B that is fed from the silo B and measured to obtain spodumene mineral powder. The friction coefficient is tested to be 0.09, the apparent viscosity is 302, and the particle size distribution is shown in Table 2. The values ​​in the table are the screening rates corresponding to the particle size.

[0047] Table 2 Screening rate of product powder

[0048] 8 points (%) 20 points (%) 40 points (%) 100 points (%) 200 points (%) 300 points (%) 100 99.8 94.5 50.2 46.6 40.5

[0049] From the above particle size distribution, it can be clearly seen that the particle size distribution is shifting towards polarization, that is, expanding the particle size difference between mineral powders, reducing the friction between particles of the same size, and improving the fluidity of inorganic mineral powders.

[0050] Based on Example 1, the following Groups 1 to 3 are set to compare the many parameter changes of Example 1. The specific setting methods and test results are shown in the specific implementation methods and tables of the following Groups 1 to 3.

[0051] Group 1

[0052] The specific operation steps are the same as those in the above-mentioned embodiment 1, except that the ratio between powder B and powder C is 1:1.

[0053] The solid content of the product powder was controlled at 65%, the friction coefficient was measured to be 0.5, the apparent viscosity was 760, and the particle size distribution was analyzed as follows: After mixed analysis, the particle size distribution of the product powder was shown in Table 3. The values ​​in the table are the screening rates corresponding to the particle sizes.

[0054] Table 3 Screening rate of product powder

[0055] 8 points (%) 20 points (%) 40 points (%) 100 points (%) 200 points (%) 300 points (%) 100 100 94.5 92.2 70.1 59.5

[0056] Group 2

[0057] The specific operation steps are the same as those in the above-mentioned embodiment 1, except that the particle size of the powder C after further grinding is 60wt% of 350-600 mesh, and 40wt% of 600 mesh.

[0058] The solid content of the product powder was controlled at 65%, the friction coefficient was measured to be 0.32, the apparent viscosity was 561, and the particle size distribution of the product powder was obtained through mixing analysis as shown in Table 4. The values ​​in the table are the screening rates corresponding to the particle sizes.

[0059] Table 4 Screening rate of product powder

[0060] 8 points (%) 20 points (%) 40 points (%) 100 points (%) 200 points (%) 300 points (%) 100 99.7 95.2 57.9 50.6 47.5

[0061] Group 3

[0062] The specific operation steps are consistent with the above-mentioned embodiment 1, and the first component and the second component are obtained when the first-level classification spray pressure of the wind classifier is controlled at 350-400KPa. The third component is obtained when the second-level classification spray pressure of the wind classifier is controlled at 250-280KPa, and the fourth component and the fifth component are obtained when the third-level classification spray pressure of the wind classifier is controlled at 200-230KPa, and five components with different particle sizes are obtained, wherein the particle size distribution is shown in Table 5, and the values ​​embodied in the table are the screening rates corresponding to the particle sizes.

[0063] Table 5 Screening rate of 5 silos

[0064] 8 points (%) 20 points (%) 40 points (%) 100 points (%) 200 points (%) 300 points (%) Supplier 1 80 50 0.00 0.00 0.00 0.00 Caterer 2 100 97.02 89.21 0.00 0.00 0.00 Servants 3 100 99.02 97.31 95.43 0.00 0.00 Servants 4 100 100 100 99.02 89.21 10.00 Servant 5 100 100 100 100 100 96.34

[0065] The solid content of the product powder was controlled at 65%, the friction coefficient was measured to be 0.47, the apparent viscosity was 652, and the particle size distribution was analyzed as follows: After mixed analysis, the particle size distribution of the product powder was shown in Table 6. The values ​​in the table are the screening rates corresponding to the particle sizes.

[0066] Table 6 Product screening rate

[0067] 8 points (%) 20 points (%) 40 points (%) 100 points (%) 200 points (%) 300 points (%) 100 99.8 95.1 52.9 56.2 61.5

[0068] Group 4

[0069] Taking spodumene as an example, the original inorganic mineral powder preparation process is used for preparation: the spodumene stored in the raw material warehouse is dropped onto a belt scale with a metering function through a raw material discharge valve, and transported to the top of the crusher, and the material is dropped into the crusher inlet by gravity. After the spodumene falls into the crusher, the speed is adjusted to 70-80%, the linear speed is controlled at 120m / s, and the spodumene particles are crushed by the high-speed rotating hammer;

[0070] The crushed spodumene mineral is directly ground with the first-generation grinding equipment (ball mill) and the mixed liquid. After being ground into powder, various parameters of the product are tested. It is found that the average solid content of the product powder obtained by the original powder making process is 59%, the friction coefficient is 0.89, and the apparent viscosity is 900.

[0071] The friction coefficient, viscosity and other parameters of the above embodiments and groups 1-4 are summarized in Table 7:

[0072] Table 7 Test results

[0073]

[0074]

[0075] Through the above experimental data analysis, the following conclusions can be drawn by comparing Example 1 with each group:

[0076] (1) Compared with Group 1, Example 1 is just that the ratio of powder B to powder C is not controlled within the range required by the scheme of the present invention, so it cannot achieve the result of improving the fluidity of the mineral powder, especially the compression degree and friction coefficient will be affected. The reason is that the proportion of powder C in Group 1 is too large, resulting in powder B and powder C being in a uniform distribution state, unable to play a filling state between particles, and unable to reduce the friction between particles in the powder.

[0077] (2) Compared with Example 1 and Group 2, the particle size distribution of powder C is not controlled within the range required by the scheme of the present invention, and the result of improving the fluidity of the mineral powder cannot be achieved. In particular, the friction coefficient will be affected. The reason is that the powder C in Group 2 is ground too finely, causing the gaps between the particles of powder B to be overfilled by the powder C, thereby increasing the friction between the particles in the powder.

[0078] (3) Compared with Group 3, Example 1 shows that since the injection pressure of each wind force classification is not controlled within the range required by the scheme of the present invention, it is not possible to separate the five particle size components into corresponding particle sizes according to the predetermined requirements, thereby affecting the subsequent particle size distribution of powder B and powder C, causing the particle sizes of powder B and powder C to increase, and the gaps between the particles of powder B and powder C cannot be fully filled, thereby increasing the friction between the particles in the powder. Therefore, it is also impossible to achieve a good result of improving the fluidity of the mineral powder.

[0079] In summary, by comparing the corresponding parameters of Example 1 with Group 1, Group 2, and Group 3, it can be seen that in the scheme of the present invention, it is very important to strictly control the ratio and particle size distribution of materials B and C, because only in this way can material C be fully filled into the gaps between the particles of material B to reduce the friction between the particles, and ultimately achieve the purpose of improving the fluidity of the inorganic mineral powder.

[0080] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.

Claims

1. A production method for improving the fluidity of inorganic mineral powder, characterized in that: The steps include: The inorganic mineral raw material is crushed to achieve a crushing rate of more than 90%, and then inorganic mineral powders of different particles are collected by classification using gravity and buoyancy, wherein 100wt% of the collected powder A has a particle size of less than 20 mesh, and is returned to be combined with the inorganic mineral raw material for crushing, and the collected powder B has a particle size of 20-120 mesh accounting for ≥80wt%, and the powder C has a particle size greater than 100 mesh accounting for ≥80wt%, and the mass ratio of powder B to powder C is controlled between (8:2) and (6:4); The powder C is further ground until the particle size is greater than 300 mesh and accounts for more than 80wt%, and then mixed with the powder B; In the process of classification by gravity and buoyancy, the falling material is first divided into 5 components by accelerating jet, and then the powders of different components are further sieved according to the mesh size to obtain powder A, powder B, and powder C, so as to improve the accuracy of the powder particle size distribution in the whole process; The injection rate of the accelerated jet is adjusted by fixing the injection air volume and adjusting the injection pressure of 150-300KPa, so that it is divided into 5 components according to the particle size through different injection rates, wherein the particle size of the first component is less than 20 meshes, the particle size of the second component is 20-40 meshes, the particle size of the third component is 40-100 meshes, the particle size of the fourth component is 100-200 meshes, and the particle size of the fifth component is greater than 300 meshes; Powder A is obtained by mixing particles of the first component and the second component with a size smaller than 20 mesh, particles of the second component with a size larger than 20 mesh, particles of the third component and the fourth component with a size smaller than 120 mesh, and powder B is obtained by mixing the remaining fourth component and the fifth component to obtain powder C. The fixed injection air volume for each classification is 20000Nm 3 / h, when the first-stage graded injection pressure is controlled at 300-350KPa, the particle size of the first component is less than 20 mesh, and the particle size of the second component is 20-40 mesh; When the secondary graded injection pressure is controlled at 200-230 KPa, the particle size of the third component is 40-100 mesh; The three-stage graded injection pressure is controlled at 150-180 KPa, the particle size of the fourth component is 100-200 mesh, and the particle size of the fifth component is greater than 300 mesh.

Citation Information

Patent Citations

  • Flotation tailing dry-type separation high pressure air stream grinding powder recycling process

    CN101693249A

  • Color tuner, imaging method and processing cassette

    CN1338663A

  • Crushing system for manufacturing aggregate

    JP2004141713A